Friday
April 18, 2014

Homework Help: Algebra

Posted by Sandrine on Wednesday, September 16, 2009 at 6:42pm.

I multiplyed x^2-2x+2 times x^2+2x+2. The book suggested the order this be done in as: x^2(x^2-2x+2) then 2x(x^2-2x+2) then 2(x^2-2x+2), with the result being x^4+4. However, I wondered if this could be done in reverse. So I multiplyed x^2(x^2+2x+2), then -2x(x^2+2x=2) then 2(x^2+2x+2). The result however was different. I'm not sure if it was just a computational error or if you really can't do it this way. If you can only do it the first way, why? Thanks!!!

Answer this Question

First Name:
School Subject:
Answer:

Related Questions

Rational Expression - (x+1/2x-1 - x-1/2x+1) * (2x-1/x - 2x-1/x^2) (x+1/2x-1 - x-...
TO KIM - can you help me with this |2x - 3|^2 - 6|2x - 3| + 5=0 I know you are ...
Math33333 - Please help me! Problem: x+2 x-3 _________ - _________ 2x^2+5x+2 2x^...
Algebra - Need help with this problem, 2x+y=6 solve for y 2x+y=6 subtract 2x ...
Dividing Rational Expressions - x^3-8/x^2-4 divided by (x^2+2x+4)/(x^3+8). This ...
math - how many times does the graph of y= 2x squared -2x+3 intersect the x-axis...
Math - Null factor law and factoriising: 2x^2+7x=0 X(2x+7)=0 X=0 or 2x+7=0. ( ...
Algebra help - Find (fog)(x)and (gof)(x)if f(x)=x-x^2 and g(x)= 2x+3. Okay so I ...
Math - Prove each identity: a) 1-cos^2x=tan^2xcos^2x b) cos^2x + 2sin^2x-1 = sin...
calculus - So I am suppose to evaulate this problem y=tan^4(2x) and I am ...

Search
Members